Winning urban competition with a social agenda: The competition imaginary in Viennese urban development plans - Carina Altreiter; Susanna Azevedo; Laura Porak; Stephan Pühringer; Georg Wolfmayr (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2022)
In the last decades many scholars have studied urban competition and entrepreneurial urban policies. Coming from the evolving field of competition research, we are interested in how urban competition is constructed and, for this purpose, examine the competition imaginary of Vienna, a city known less for its entrepreneurial policies than for its social welfare policies. The paper employs critical discourse analysis of Viennese policy papers from 1985-2015, a period particularly shaped by the process of competitization. The analysis shows that Vienna's social and welfare policies are also decisive for the city's positioning in urban competition and rankings.
Keywords: 330; urban competition; urban policies; Vienna; competition imaginary; extra-economic competition; entrepreneurial city; social welfare policies